Factors Affecting the Quality of Life of Breast Cancer Patients - Alifka Deti Sri Maharani; Dwi Sarwani Sri Rejeki; Siwi Pramatama Mars Wijayanti (Disease Prevention and Public Health Journal, 2023)
Background: Breast cancer is the most frequently diagnosed cancer and the leading cause of cancer death among women worldwide in 2020. This systematic review aims to identify the factors that affect the quality of life of breast cancer patients so that the results of this systematic ventilation can help health professionals develop appropriate interventions. Method: This systematic review followed the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. This study aims to identify the factors that affect the quality of life of breast cancer patients. A comprehensive search was performed across several databases, including PubMed, Embase, Scopus, and Web of Science. The search was limited to studies published between 2019 and 2022, which were written in English. Results: Factors that affect the quality of life of breast cancer patients include age, education level, social support, psychological stress and anxiety, economic status, depression, and physical symptoms. Conclusion: Several factors can affect the quality of breast cancer patients, so the patient needs support from the family and health policies from the government in their treatment.